Sosialisasi Pentingnya Lingkungan Hijau Bagi Siswa-Siswi SMP Oikoumene Kota Sorong Provinsi Papua Barat Daya - Pattiwael, Maya; Madina, La Ode; Alfons, Burmanus; Kalagison, Melvi; Masauna, Risna; Wattimena, Brian Henrry; Rumaropen, Stevandri; Mustamu, Alessandro; Maay, Herna (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
Student’s lack of understanding about the importance of a green environment is the reason for carrying out community service activities at Oikoumene Middle School, Sorong City. Socialization can be a solution to provide education for students with the aim for increasing awareness and knowledge about the important of a green environment for them and instilling an attitute of concern for the surrounding environmrnt. The socialization was attended by 26 participants. The material is presented in Powerpoint form with the help on infocus. The socialization was carried out in 3 stages, namely the preparation, implementation and evaluation stages. Based on the results of the pre-test and post-test, it can be concluded that the participants experienced increased knowledge and were able to understand the importance of a green environment, especially in school areas after receiving the socialization material. Apart from that, as a first step in implementing a green environment at the PKM location, tree saplings were handed over to be planted around the school area